DIPLOMASI ISLAM INDONESIA-TIONGKOK - Abid Rohman; Ridha Amaliyah (The Indonesian Islamic Studies and International Relations Association (Insiera), 2019)
This research aims to understand the influence of Islam in Indonesia-China public diplomacy perspective, to determine the roles of non-state actors, as well as to identify its opportunity and challanges. This research conducts a qualitative-descriptive approach. The researcher found that Islam influences both countries’ public diplomacy in art and cultural field as well as public diplomacy practices. Admiral Cheng Hoo holds major roles in the spread of Islam that time. The roles of non-state actors are crucial when conducting people-to-people approach: as dialogue and cooperation partner, and as promotor. Both countries has enjoyed advantages being each other’s partner in various fields. The role of promotor is beared mainly by Muhammadiyah and Nahdatul Ulama in disseminating the core value of Islam which is peace and justice. The opportunity in actualizing a sustainable cooperation between Indonesia- China is wide open in the near future due to the spirit of Belt and Road Initiatives. Meanwhile, the challenges are quite solid. The fact that Islam is minority in China and the lack of references leads to misperception among Chinese people; the domination of China in economy that are considered as a threat by most Indonesian people; the long-existed negative perception toward Indonesian-Chinese descendants; as well as Indonesia’s double identity dilemma (pluralist and religious state) in formulating public diplomacy are several defiances that must be solved in achieving a harmonious relations between Indonesia and China.